Attosecond time-resolved streaked photoemission from Mg-covered W(110) surfaces - Liao, Qing; Thumm, Uwe (My University, 2015)
We formulate a quantum-mechanical model for infrared-streaked photoelectron (PE) emission by ultrashort extreme ultraviolet (XUV) pulses from an adsorbate-covered metal surface, exposing the influence of microscopic PE dispersion in substrate and adsorbate on the interpretation of streaked photoemission spectra and photoemission time delays. We validate this numerical model first by reproducing measured relative photoemission delays (a) between valence-band and 2p-core-level (CL) PEs emitted from clean Mg(0001) surfaces and (b) between conduction-band (CB) and 4f-CL PEs from clean W(110) surfaces at two XUV-pulse central photon energies. Next, applying this model to ultrathin Mg adsorbate layers on W(110) substrates, we reproduce (i) the measured nonmonotonic dependence of relative photoemission delays between CB and Mg(2p) PEs and (ii) the monotonic dependence of relative delays between W(4f) and Mg(2p) PEs in a recent experiment [S. Neppl et al., Nature (London) 517, 342 (2015)].